Peningkatan Kecerdasan Logika Terhadap Efektifitas Pembelajaran di Kelas Berbasis Problem Solving - Hanik, Hanik; Winata, Aliahardi; Muttaqin, Zedi; Isnaini, Isnaini; Saddam, Saddam; Azwar, Wahyu (Universitas Muhammadiyah Mataram, 2025)
This study aims to analyze the impact of logical intelligence on the effectiveness of problem-based learning strategies. The research adopts the Systematic Literature Review (SLR) method, utilizing data from 22 peer-reviewed international journal articles indexed in Google Scholar and published by various academic sources. The findings reveal that logical intelligence significantly influences the effectiveness of classroom learning strategies. Logical intelligence serves as a critical factor in enhancing students' academic outcomes, where the implementation of problem-solving approaches fosters critical and logical thinking skills essential for addressing academic challenges. By understanding these characteristics, educators can design appropriate teaching strategies, establish inclusive learning environments, and provide opportunities for students to contribute optimally. Additionally, the study highlights the importance of integrating traditional and digital instructional media to enrich students' learning experiences. This combination not only increases student engagement but also ensures that the learning process remains relevant and meaningful. The conclusions emphasize that incorporating logical intelligence into problem-based learning strategies can substantially enhance classroom learning effectiveness, offering valuable insights for educators aiming to improve pedagogical practices.